Studies of herpes virus latency in the sensory spinal ganglia of rabbits. - Tosolini, F. A. (Cambridge University Press, 1982)
Experimental latent herpes infection of rabbit dorsal root ganglia (DRG) is reported. The simian herpes virus used was derived from fatal natural infection in owl monkeys and has limited neurotropism in the rabbit. Following intradermal injection of the flank it causes a local lesion followed only by dorsal root ganglionitis; segmental paraesthesia and/or sensory loss going on to clinical recovery. Methods were developed for mapping sensory losses. Virus could be immediately re-isolated from skin or DRG homogenates in the acute (first week) stage but from 8-550 days by DRG organ culture only. Spontaneous recurrence does not occur but reactivation can be provoked. The system provides an improved analogue model for the study of the pathogenesis and symptomatic treatment of herpes zoster.